From Practice to Field: A Multilevel Model of Practice-Driven Institutional Change - Smets, Michael; Morris, Tim; Greenwood, Royston (Academy of Management Journal, 2012)
This article develops a model of practice-driven institutional change—or change that originates in the everyday work of individuals but results in a shift in field-level logic. In demonstrating how improvisations at work can generate institutional change, we attend to the earliest moments of change, which extant research has neglected; and we contrast existing accounts that focus on active entrepreneurship and the contested nature of change. We outline the specific mechanisms by which change emerges from everyday work, becomes justified, and diffuses within an organization and field, as well as precipitating and enabling dynamics that trigger and condition these mechanisms.